UTILITY OF HEART TYPE FATTY ACID BINDING PROTEIN (H-FABP) POINT OF CARE TEST IN THE EARLY HOURS OF STEMI COMPARED WITH TROPONIN-I IN PAKISTANI POPULATION - Abbasi, Walid Ahmad; Saleem, Muhammad; Rashid, Shahid; Kayani, Azhar Mahmood (Journal of Ayub Medical College Abbottabad, 2017)
Background: Acute coronary syndrome remains a dominant cause of high morbidity and mortality despite advancements in treatment This study was conducted to examine the utility of point-of-care test of heart-type fatty-acid binding protein (h-FABP) and compare it with the point-of-care test of cardiac troponin I (cTnI) in the first 06 hours of STEMI. Methods: This cross-sectional, comparative study which was conducted in Rawalpindi institute of cardiology, Rawalpindi, Pakistan, from January to June 2015. Serum samples of 125 patients with the diagnosis of STEMI, presenting with chest pain of less than 6 hours’ duration, were analysed for quantitative and qualitative determination of h-FABP and cardiac troponin I (cTnI) using rapid immunochromatographic technique in the emergency department. Samples were taken at presentation and after 12 hours. Results: Out of 125 patients, 112 were males and 13 were females with a mean age of 54.26±9.53 years. The average symptom-to-sample time was 3.19±1.44 hours (median 3 hours). Mean h-FABP levels were significantly higher than the mean cTnI levels (29.10±30.66 vs 0.94±2.02; p=0.000). Overall, H-FABP was more sensitive than cTnI (72% vs 26.4%). The sensitivity of cTnI within 0-2, 2-4, and 4-6 hours of symptom onset was calculated to be 0%, 17.7%, and 75.9%, whereas sensitivity of H-FABP was 35.3%, 79.03% and 100% respectively. There was not a single patient who was cTnI positive and H-FABP negative as compared to 57 patients who were FABP positive and cTnI negative. Conclusion: h-FABP is a promising cardiac biomarker for the early identification of myocardial ischemia and infarction. It could be a superior biomarker for earlier detection of ACS and screening of patients with non-cardiac chest pain. Keywords: Heart type fatty acid protein; ST-segment elevation myocardial infarction; Troponin I, STEMI